Explicit travelling wave solutions of two nonlinear evolution equations - ERTAŞ, Abdulkadir; MIZRAK, Mustafa (My University, 2014)
In this paper, we applied the sine-cosine method and the rational functions in exp(ksi) method for the modified Kawachara equation and the Damped Sixth-order Boussinesq Equation, respectively. New solitons solutions and periodic solutions are explicitly obtained with the aid of symbolic computation.
Keywords: Travelling Wave Solutions; The Sine-Cosine Method; The rational Functions in Exp(ksi) Method